Vesicular Stomatitis Virus-induced Immune Suppressor Cells Generate Antagonism Between Intratumoral Oncolytic Virus and Cyclophosphamide - Willmon, Candice (Nature Publishing Group, 2011)
Despite having potent oncolytic activity, in vitro, direct intratumoral injection of oncolytic vesicular stomatitis virus (VSV) into established AE17ova mesothelioma tumors in C57Bl/6 mice had no therapeutic effect. During studies to combine systemic cyclophosphamide (CPA) with VSV to suppress the innate immune reaction against VSV, we observed that CPA alone had highly significant antitumor effects in this model. However, against our expectations, the combination of CPA and VSV consistently reduced therapeutic efficacy compared to CPA alone, despite the fact that the combination increased intratumoral VSV titers. We show here that CPA-mediated therapy against AE17ova tumors was immune-mediated and dependent upon both CD4 T cells and natural killer (NK) cells. However, intratumoral VSV induced a transforming growth factor-β (TGF-β)-dependent suppressive activity, mediated by CD11b(+)GR-1(+) cells that significantly inhibited both antigen-specific T-cell activation, and CPA-activated, NK-dependent killing of AE17ova tumor cells. Overall, our results show that treatment with oncolytic viruses can induce a variety of immune-mediated consequences in vivo with both positive, or negative, effects on antitumor therapy. These underexplored immune consequences of treatment with oncolytic viruses may have significant, and possibly unexpected, impacts on how virotherapy interacts in combination with other agents which modulate antitumor immune effectors.